A new breeding population of Mediterranean Gulls Larus melanocephalus in the species' main wintering area maintains independent spatial dynamics. (18th November 2015) - Carboneras, Carles; Dies, José Ignacio
Abstract : We studied a newly established breeding population of the range‐expanding Mediterranean Gull Larus melanocephalus in eastern Spain, situated in close proximity to the species' main wintering area. By investigating the origin, population composition and wintering area of the new breeders, we found that recruitment from locally wintering birds was unlikely and that the emerging colonies were probably attracting birds from populations wintering 700–1200 km away in Portugal and southern Spain. Our findings reveal that expanding populations may follow their own dynamics, independently of other populations of the same species, and may consist of different individuals altogether.